Death by arts and crafts - Morgan, Alexis (Morgan, Alexis. Abby McCree mystery., 2023)
"As the newest member of the Snowberry Creek City Council, perpetually overextended Abby McCree is picked to liaise between the council and the new planning committee for the town's first ever arts and crafts fair. As far as gigs go, it's a fun one--Abby's spending the weekend tooling around Washington State, checking out similar fairs with her two besties, coffee shop owner Bridey Roker and ceramic artisan Dayna Fisk. As Abby spreads the word about Snowberry Creek's fair, recruiting the industry's biggest movers and makers, the trip feels like a glittering success. But then, someone is found murdered at one of the events and vendors begin disappearing amid suspicious circumstances. Abby's determined to keep her hands clean until Dayna finds herself stuck at the top of the suspect list. Now, Abby must weave the clues together and clear her friend's name before the killer claims another victim--maybe even Abby herself..." -- Provided by publisher.